RELATIVE OUTPUT FACTOR (ROF) OF GAMMA KNIFE’S MEASUREMENT USING IONIZATION CHAMBER AND GAFCHROMIC FILMS - nazaroh nazaroh; Okky Agassy Firmansyah; Ade Rizky Setiadi; Irhas Irhas; Elia Sudiatmoko (Badan Standardisasi Nasional, 2021)
The important things on Leksell Gamma Knife (LGK) is determination of Relative Output Factor (ROF), which is required for beam data collection (BDC) process, as an input value to the Treatment Planning System (TPS). The ROF is also needed to traceability of dosimetry measurements and patient safety. ROF measurements on LGK using PTW PinPoint 3D ionization chamber: 0.016 cm3, PTW Semiflex: 0.125 cm3, and Exradin A16: 0.017 cm3 at collimators 4, 8 and 16 mm. and gafchromic films. ROF values obtained in hospital-A, using PTW PinPoint 3D was: [(1.00 ± 0.002)], [(0.80 ± 0.02]); [(0.42 ± 0.002)]; and using Exradin A16 [(1.00 ± 0]; [(0, 87 ± 0)]; [(0.69 ± 0.0002)]. And using gafchromic films was: [(1.00 ± 0.006]; (0.96 ± 0.005); (0.86 ± 0.06)]; respectively for collimators 4, 8 and 16 mm, and Measurement of ROF in hospital-B using using a PTW PinPoint 3D was: [(1 ± 0); (0.75 ± 0); and (0.33 ± 0)] and using Exradin A16 was: [(1; 0.87; and 0.69)] and gafchromic films was: [(1.00 ± 0.03); (0.98 ± 0.045); and (0.85 ± 0.09)]; The results of ROF’s measurement were compared with the ROF values of Novotny, et al (2009) and TPS. The Gafchromic’s ROF values were relatively closer than both of them, while the ROF value of ionization. chamber at 4 mm collimators was relatively lower, because measurement in a small field occurs an averaging effect volume and lack of lateral charge particle equilibrium (LCPE).